Financial Report Application Using the MVC Method at the Pampemi Shop Bag Store in Prabumulih City - Nesya Olivia; Khana Wijaya; Rishi Suprianto (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The Pampemi Shop store was established on May 25, 2022, because it started when the owner saw one of the live broadcasts of someone offering his products through social media, plus the owner's interest in fashion. The Pampemi Shop is located on Jalan Tenggamus, Muara Dua Village, East Prabumulih City, Prabumulih City. The Pampemi Shop store still uses a manual system by using a ledger in financial reporting, therefore the Pampemi Shop in Prabumulih city needs an application fast and precise financial statements so that the management of financial statements can be easily used by employees. Therefore, the author wants to create a financial reporting application using PHP and MySQL programming. The result of this study is to make it easier for the components in the Pampemi Shop store to make financial reports.